Post-pandemic: outcomes and prospects of the digitalisation of higher education - T. N. Yudina; N. N. Semochkina (Цифровая социология)
The article attempts to analyse the interim results of digitalisation of the Russian higher education system in the post-pandemic period. The research methods include an analysis of regulatory documents, statistical analysis of data gathered by the Federal State Statistics Service, and a secondary analysis of results from research centres of the Higher School of Economics, Plekhanov Russian University of Economics, and others. The main findings are related to the analysis of dynamics of indicators responsible for transformation of the social space in the higher education system during digitalisation. The authors view the digitalisation of higher school as a factor that perpetuates social inequality and stimulates the development of its new forms. They conclude that maintaining distance learning in universities contributes to communication barriers within the student community and between students and faculty as well. Slow increase in the digital literacy of teachers is emphasised. During the analysis, the authors conclude that the transformation of higher school through digitalisation is progressing at quite slow rate due to unhurried provision of universities with financial, technical, and personnel resources necessary for the digital transition. The novelty of the work lies in documenting the results of the transformation of social relations within the higher education system during digitalisation and defining its characteristic features, including the readiness of participants of the educational process to implement specific state vectors of the transformation of the Russian higher education